Optimization of biodiesel production and engine performance from high free fatty acid Calophyllum inophyllum oil in CI diesel engine - Ong H.C.; Masjuki H.H.; Mahlia T.M.I.; Silitonga A.S.; Chong W.T.; Leong K.Y. (2023)
In the present study, crude Calophyllum inophyllum oil (CCIO) has been evaluated as a potential feedstock for biodiesel production. C. inophyllum oil has high acid value which is 59.30 mg KOH/g. Therefore, the degumming, esterification, neutralization and transesterification process are carried out to reduce the acid value to 0.34 mg KOH/g. The optimum yield was obtained at 9:1 methanol to oil ratio with 1 wt.%. NaOH catalyst at 50 C for 2 h. On the other hand, the C. inophyllum biodiesel properties fulfilled the specification of ASTM D6751 and EN 14214 biodiesel standards. After that, the C. inophyllum biodiesel diesel blends were tested to evaluate the engine performance and emission characteristic. The performance and emission of 10% C. inophyllum biodiesel blends (CIB10) give a satisfactory result in diesel engines as the brake thermal increase 2.30% and fuel consumption decrease 3.06% compared to diesel. Besides, CIB10 reduces CO and smoke opacity compared to diesel. In short, C. inophyllum biodiesel can become an alternative fuel in the future. © 2014 Elsevier Ltd. All rights reserved.